O lugar feminino na escola: um estudo em representações sociais - Andrade, Daniela Barros da Silva Freire (2006)
This study is intended to know the social representations (MOSCOVICI, 1978) that circulate in different contexts of communication of the social actors in a school community. It is about school spaces potentially feminine. The feminine place in this research is understood as based on three especialists discourse. The discourse moved to three indicators, named: 1. an opening to the other, 2. the active wait, and 3. the rebel of fecund imaginary. These indicators, articulared to the concept of narrative space (SENNETT, 1990) , were taken as quantifiers of the feminine themata in its socio-spatial manifestation. The findings presented refer to the context of a public school in Cuiabá in the state of Mato Grosso in Brazil where observations and interviews with 44 students, 10 teachers and 7 school employees were carried out. For the analysis of the information it was used the techniques of analysis of comprehensive, analysis of content (BARDIN, 1995) and lexical analysis (REINERT, 1986). The results indicate that the social representations the different groups construct of the school places are connected with the representations of theirselves, of their group and the people who occupy these places. The school places with great potential narrative and, therefore, feminine places, like the school sports square and the bathroom are associated to the meaning of transgressions that seems to have extensions to their users who are recognized as transgressive. The expression of the feminine in the school converges to the direction of against normative behaviors that, if assumed by the informers subjects would send them a social disapproval.The school, consisting with its bases in the feminine themata, is expressed as a wordless school, a silent school what does not mean that might be understood as an inoperative school. It seems to live among the breaches of the instituted processes, in the mute zone as Abric considers (2003) the hidden and strategically not confessional face of a grid of meanings that participates of the symbolic construction and of the identification processes that involve the social school and its actors